The Effect Of Service Quality And Customer Relationship Management On Customer Satisfaction At PT. Setra Sari : (Study on Partners in Jabodetabek) - Komarudin Komarudin; Widya Candra Dewi (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to determine the effect of service quality and customer relationship management on PT Setra Sari (Study on Jabodetabek Partners). This study used a population of 53 people and a sample of 53 respondents. The research methodology used is quantitative research methods. Then the analysis tests used are data quality tests, linear regression tests, correlation tests, determination coefficient tests and partial and simultaneous hypothesis tests. Based on the results of the study (1) Service quality has a positive and significant effect on customer satisfaction at PT Setra Sari, Jabodetabek Partners study. This is proven by the results of partial hypothesis tests obtained sig values ??<0.05 and t count values ??> t table (0.000 <0.05 and 3.828 > 1.675). (2) Customer relationship management has a positive and significant effect on customer satisfaction at PT Setra Sari Mitra Jabodetabek study, proven by the results of partial hypothesis testing which obtained sig values ??< 0.05 and t count values ??> t table (0.007 < 0.05 and 2.821 > 1.675). (3) Service quality and customer relationship management have a positive and significant effect on customer satisfaction at PT Setra Sari Mitra Jabodetabek study, proven by the results of simultaneous hypothesis testing which obtained sig values ??< 0.05 and F count values ??> F table (0.000 < 0.05 and 14.727 > 3.18).